Geomagnetic field behavior during the Iceland Basin and Laschamp geomagnetic excursions: A simple transitional field geometry? - Laj, Carlo; Kissel, Catherine; Roberts, Andrew (Geochemistry, Geophysics, Geosystems, 2006)
International audience We present four new records of the Iceland Basin Excursion (IBE) and five new records of the Laschamp Excursion (LE) obtained from rapidly deposited marine sediments in the North Atlantic Ocean, the Nordic Seas, the Gulf of Mexico, the South China Sea, and the southern Indian Ocean. Marked minima in relative paleointensity correspond with the paleomagnetic directional changes associated with all of the excursion records. The virtual geomagnetic pole (VGP) paths of the four IBE records are all similar. The VGPs move southward over Europe and Africa, reaching the southern hemisphere (three reach Antarctica), and then move to more eastern longitudes before returning northward over Australia and east Asia, describing a large counterclockwise loop. The same VGP pattern is observed in other published records. The VGP paths observed for the LE are similar to those of the IBE; however, they loop clockwise instead of counterclockwise. Despite the different sense of looping, the marked similarity among the paths for the two excursions suggests that a similar, relatively simple geometry dominated the transitional field during both the IBE and the LE. Similar dynamo mechanisms must therefore have been active in the Earth's core for both excursions. The duration of the excursions is estimated at <2,000 years, which supports the suggestion that a difference exists between the mechanisms for excursions and reversals. However, the coincidence of the longitudinal bands for VGPs associated with excursions compared to some reversal paths could also indicate an inherent link between the mechanisms for reversals and excursions.